A organização da educação física na educação infantil no DEI/CEPAE/UFG - Martins, Poliana Carvalho (2019)
This research starts from the hypothesis that teaching Physical Education in Early Childhood Education favors the development of children. The study arises from the problematization: "How to organize or teach physical education for childrens in childhood education?” and had as its general objective: "to organize or teach physical education for children from um to two years in the DEI/CEPAE/UFG. The research starts from the historical experiences of the Department of Early Childhood Education of CEPAE/UFG (DEI/CEPAE/UFG), identifying the insertion and function of physical education and its graduate in this space. Assumes Dialectical and Historical Materialism (MARX, 1999, 2016) as a method for analyzing the data obtained by the instruments: literature review, documentary analysis, interview, questionnaire, routine participant observation and development of a didactic sequence with the gymnastics theme. The analyzes of Physical Education (EF) or Coletivo de Autores (1992) and those on the Childhood Education (EI) to Historical and Cultural Theory (VIGOTSKI, 1984, 1998, 2010; LEONTIEV, 2006; ELKONIN, 1987). Through the literature review it was possible to conclude that although PE has been present as a compulsory component of Basic Education, since the 1996 LDB, it does not seem to have been effectively consolidated in IS. Interview analyzes and documents show that physical education has been present at DEI/ CEPAE/UFG since its inception. The pedagogical sequence performed tried the guiding principles for the pedagogical practice of the PE teacher and sought to adapt the teaching to the children's guide activity, establishing the complexification of the children's motor challenges, as well as collective work with the pedagogical teacher. The research originated an educational product in the kindergarten: a didactic sequence with guiding principles for the specific teaching of gymnastics, developed in 2017.